Enhancing Huber's evaluation framework for teacher professional development programme - Wendy Hiew; Murray, Jill (Routledge, 2021)
This paper presents an enhanced evaluation framework for teacher professional development programmes, which is based on one originally proposed by Huber in 2011. This paper draws on a study on the Professional Up-skilling of English Language Teachers (ProELT) programme in Sabah (Borneo), Malaysia. The study adopted a mixed methods exploratory sequential design using a questionnaire survey, individual interviews and a focus group discussion. Based on the findings from the study, four new components have been added to Huber’s original framework, namely (1) selection of participants, (2) incorporation of the Adult Learning principles, (3) follow-up support, and (4) assessment of programme impact. This enhanced framework has significant contributions to make to programme designers and programme providers, in providing them with additional guidelines to consider when designing the pre-, ongoing and post-phases of a teacher professional development programme.